The Impact of Financial Literacy Training for Migrants - Gibson, John (The World Bank, 2012)
Remittances are a major source of external finance for many developing countries but the cost of sending remittances remains high for many migration corridors. International efforts to lower costs by facilitating the entry of new financial products and new cost comparison information sources rely heavily on the financial literacy of migrants. This paper presents the results of a randomized experiment designed to measure the impact of providing financial literacy training to migrants. Training appears to increase financial knowledge and information seeking behavior and reduce the risk of switching to costlier remittance products. But it does not change either the frequency or level of remittances